Combination Potential of Some Bacteria Insulated From LMO Banana Stem Bud as A Bio-Control Against, Spodoptera litura Fabricius - Yulensri, Yulensri; Noveri, Noveri; Arneti, Arneti; Murti, Kresna (Akta Agrosia, 2021)
S. litura F pests are widespread in Indonesia covering 22 provinces with an average attack area of 11,163 ha/year.  This pest is polyphag causing damage to the leaves (defoliation) with crop loss can reach 85% even to failed miserably.  The application of biotechnology derived from local resources is a very appropriate alternative to controlling S. litura, namely Bacillus cereus strain ATCC 14579,  Bacillus subtillis subsp. subtilis strain 168  Bacillus siamensis strain KCTC13613, Azotobacter sp. and Pseudomonas fluorescens isolated from the LMO banana stem bud.  The aim of this study is to determine the potential of 5 types of bacteria that were consortified as S. litura pest bio-control agents. The research consisted of stages, namely 1) bacterial compatibility test which would be consortified; 2) invitro bacterial consortium potential test on S. litura F. larvae.  The results showed that the bacteria B. cereus strain ATCC 14579, B. subtillis subsp. Subtilis strain 168 B. siamensis strain KCTC13613, Azotobacter sp. and P. fluorescens are compatible with each other so that they can be consortified. These 5 types of bacteria are single less potential as S. litura pest bio-control agents because they cause low larval mortality, but a consortium of 5 bacteria can cause larval mortality by 70% . Keywords: biocontrol agents, Spodoptera litura, bacterial consortium, LOM banana stem bud